1991
DOI: 10.1056/nejm199109053251002
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma in Italian Patients with Cirrhosis

Abstract: In the West, as in Asia, patients with cirrhosis of the liver are at substantial risk for hepatocellular carcinoma, with a yearly incidence rate of 3 percent. Our screening program did not appreciably increase the rate of detection of potentially curable tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
375
5
15

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 747 publications
(412 citation statements)
references
References 21 publications
16
375
5
15
Order By: Relevance
“…A positive association of cirrhosis of the liver in 80-90% of patients with HCC has been demonstrated in reports from Northern regions. [12][13][14][15][16][17] Oka et al 1990 18 found the yearly incidence rate of HCC in cirrhotics varies from 3% in the West 19 to as high as 11% in Japan. Tsukuma et al1990 8 in a prospective study from Japan reported liver cirrhosis and viral hepatitis as risk factors for HCC, each carrying a 3-year cumulative risk of 12.5 and 3.8%, respectively.…”
Section: What Are the Risk Factors For Hepatocellular Carcinoma In Inmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive association of cirrhosis of the liver in 80-90% of patients with HCC has been demonstrated in reports from Northern regions. [12][13][14][15][16][17] Oka et al 1990 18 found the yearly incidence rate of HCC in cirrhotics varies from 3% in the West 19 to as high as 11% in Japan. Tsukuma et al1990 8 in a prospective study from Japan reported liver cirrhosis and viral hepatitis as risk factors for HCC, each carrying a 3-year cumulative risk of 12.5 and 3.8%, respectively.…”
Section: What Are the Risk Factors For Hepatocellular Carcinoma In Inmentioning
confidence: 99%
“…Tsukuma et al1990 8 in a prospective study from Japan reported liver cirrhosis and viral hepatitis as risk factors for HCC, each carrying a 3-year cumulative risk of 12.5 and 3.8%, respectively. Colombo et al 1991 19 described that the development of HCC during the course of cirrhosis is not necessarily related to endstage liver disease. Cirrhotic liver contains various kinds of hepatocellular nodules and these nodules were known to cause HCC.…”
Section: What Are the Risk Factors For Hepatocellular Carcinoma In Inmentioning
confidence: 99%
“…Chronic hepatitis develops in 33-84% of patients with acute hepatitis C. [1][2][3][4] Once, chronicity has established, about one-third of patients develop liver cirrhosis within 15-25 years 5,6 with an annual risk of hepatocellular carcinoma in 1-4% in cirrhotic livers. [7][8][9] Several factors such as alcohol abuse, coinfection with HBV or HIV, gender or age at infection determine the highly variable course of liver disease in hepatitis C virus (HCV) infection. 5,[10][11][12] Besides, the hepatocellular injury in patients with CHC results from the host's immunemediated responses to viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, symptoms seldom develop in patients with these small tumours with the result that relatively few patients are suitable for such treatment options. There is, therefore, considerable interest in presymptomatic detection by surveillance of high-risk groups (Liaw et al, 1986;Colombo et al, 1991;Chalasani et al, 1999;McMahon et al, 2000;Mok et al, 2005). Although there is no conclusive evidence (in terms of reduction of disease-specific mortality) that surveillance is effective, it is nonetheless widely practiced (Chalasani et al, 1999) and there is no doubt that such programmes do result in the detection of small tumours (Chalasani et al, 1999;Mok et al, 2005).…”
mentioning
confidence: 99%